Contribution of next generation sequencing to the diagnosis of inborn errors of immunity in a pediatric cohort - Godinez-Zamora, Guadalupe Fernanda; Baeza-Capetillo, Patricia; Saucedo-Ramírez, Omar Josué; Del-Río-Navarro, Blanca Estela; Espinosa-Padilla, Sara Elva; Morán-Barroso, Verónica Fabiola; Aguirre-Hernandez, Jesus (Frontiers in Immunology, 2025)
Inborn errors of immunity (IEI) number more than 500 diseases, with most affected patients being children. Their precise diagnosis is hampered by overlapping phenotypes, and by their ample and varied phenotypic spectrum. We analyzed the contribution of next generation sequencing to the diagnosis of IEI in a cohort of 157 children in a referral hospital in Mexico City. Following the classification of the International Union of Immunological Societies (IUIS), patients were assigned to an IEI group before sequencing, or to an “undefined” group, if it was not possible to assign them to any of them. Patients were again classified in the IUIS groups after sequencing. The diagnostic yield was 32.48%. Before sequencing, the largest group was comprised by patients that could not be assigned to a specific IUIS group (38.35% of the cohort), while after sequencing the largest group was made by the patients where no likely molecular diagnosis was found (67.52% of the cohort). Patients that were assigned to an IUIS group were confirmed to have a disease of that same group in 31.25% of the cases, while in 10.42% the molecular diagnosis corresponded to an immunodeficiency of a different group to the one initially suggested. In 18.03% of the children that could not be assigned to an immunodeficiency group before sequencing, a molecular diagnosis was reached after sequencing. In the patients that remained without a molecular diagnosis, the possibility of new IEI genes was explored by analyzing the variants, first in a curated set of immune related genes, and then across the whole exome. However, after filtering the variants, by frequency, predicted consequence, and known biology, no new IEI candidate genes were identified. This results underscore the large impact of next generation sequencing for the correct diagnosis of IEI, and also points to the need to better understand their genetic architecture in order to increase the diagnostic yield.